Pengaruh Edukasi Kesehatan dengan Self Instructional Module Terhadap Pengetahuan Tentang Diabetes Melitus - Oktorina, Rola; Sitorus, Ratna; Sukmarini, Lestari (Jurnal Endurance, 2019)
Number of diabetes mellitus cases have been increasing every year. Diabetes mellitus patient needs to get information about diabetes mellitus at least after the diagnose were given. Nurse as an educator could give education for diabetes mellitus patient, so that there will be an upgrade of knowledge diabetes mellitus patient. Verbal education need an additional tool such as a modul, in purpose patient can re-evaluate the material that they already get. The purpose of this research is to test the impact of education using self instructional module to level of knowledge about diabetes mellitus  to diabetes mellitus patient type 2. This research using quasi experimental with one group pretest postest design with 29 person  samples in total with diabetes mellitus  type 2 diagnosis. Data collection using questionaire. Statistic analysis using wilcoxon. Research result shows that there are differences of knowledge before and after education by self instructional module (p= 0,000; α=0,05) before and after education by self instructional module. Hopefully this research can be use as health education media in an attempt to upgrade the knowledge of diabetes mellitus patient type 2.Pasien diabetes melitus perlu mendapatkan informasi tentang diabetes melitus minimal setelah ditegakan diagnosa. Perawat sebagai edukator bisa memberikan edukasi terhadap pasien diabetes melitus agar terjadinya peningkatan pengetahuan pasien diabetes. Penyampaian edukasi melalui lisan perlu ditambahkan dengan modul, agar pasien dapat meninjau kembali materi yang telah diterima. Penelitian ini bertujuan untuk mengetahui pengaruh edukasi dengan menggunakan self instructional module terhadap tingkat pengetahuan tentang diabetes melitus pada pasien diabetes melitus tipe 2. Penelitian ini menggunakan desain quasi experimental dengan one group pretest postest dengan jumlah sampel 29 orang dengan diagnosa diabetes melitus tipe 2, pengumpulan data menggunakan kuesioner. Analisis statistik menggunakan wilcoxon test. Hasil penelitian menunjukkan bahwa terdapat perbedaan pengetahuan (p< 0,001; α<0,05) sebelum dan sesudah edukasi dengan self instructional module. Penelitian ini diharapkan dapat digunakan sebagai media edukasi kesehatan dalam upaya peningkatan pengetahuan pada pasien diabetes melitus tipe 2.